The Role Of Trust And Transparency In Forming Shariah Bank Customer Loyalty - Nurhayati (LP2M IAIN Palopo, 2026)
The purpose of this study is to analyze the role of trust and transparency in shaping Sharia bank customer loyalty. The method used is a literature review, examining various scientific sources, including journals, books, and publications relevant to the research topic. The data used is secondary data, analyzed descriptively and qualitatively through a process of reduction, presentation, and conclusion drawing. The results indicate that trust is a fundamental factor influencing customer loyalty because it reflects customer confidence in the integrity, security, and compliance of bank operations with Sharia principles. Meanwhile, transparency plays a crucial role in building and strengthening trust through information disclosure, clear contracts, and honest and accountable communication. Good transparency can increase customer understanding and comfort, thus encouraging the formation of long-term relationships. Trust and transparency are interconnected and simultaneously influence customer loyalty. Transparency is the foundation for building trust, while trust strengthens loyalty by increasing customer commitment and retention. However, challenges remain in its implementation, such as a lack of information transparency and suboptimal levels of customer trust. Therefore, integrating trust and transparency is key to increasing customer loyalty in Islamic banks. Therefore, a sustainable strategy is needed to improve both aspects to support the development of the Islamic banking industry.